Pesan Moral Dalam Film “KKN Di Desa Penari” (Analisis Semiotika Roland Barthes) - Sasa, Nadya Dwi Safitri; Masruroh, Dorifatul (Medio Jurnal Ilmu Komunikasi, 2024)
Films can provide education or motivation from the messages in them. Even horror films must have messages that can be taken as motivation. One of them is KKN in the Dancer Village. This film tells about students at a university in East Java who are conducting Community Service Program (KKN) in a dancer village. They carry out KKN in a village that is located in the middle of a forest and is the only village where there will certainly be many mystical phenomena and traditional customs that are inversely proportional to the habits of the city's students. From the phenomenon of the film, the researcher examines more deeply the messages and meanings in the film with a study entitled "MORAL MESSAGE IN KKN FILM IN PENARI VILLAGE (ROLAND BARTHES SEMIOTICS ANALYSIS). The purpose of this study is to find out what the moral messages are in the film KKN DI PENARI VILLAGE. Using a qualitative descriptive approach, namely photographing the social situation that will be thoroughly examined. The technique used is semiotic analysis which analyzes visuals using denotative, connotative and mythical techniques. Then it produces several moral messages, namely maintaining modesty in dress when in a new environment, speaking kindly and politely, violating the rules that have been given and committing indecent acts in prohibited places. It can be interpreted that in a film there is always a sign that leads to a meaning or message contained therein.